2023
DOI: 10.3390/biom13071070
|View full text |Cite
|
Sign up to set email alerts
|

An Update on S100A16 in Human Cancer

Abstract: S100A16 is a member of the S100 protein family. S100A16 is expressed in a variety of human tissues, although at varying levels. S100A16 expression is especially high in tissues rich in epithelial cells. mRNA and protein levels of S100A16 have been reported to be differentially expressed in the majority of human cancers. Functionally, S100A16 has been linked to several aspects of tumorigenesis, for example, cell proliferation, differentiation, migration, invasion, and epithelial-mesenchymal transition (EMT). Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…S100A16, a calcium-binding protein, is widely expressed in tumor tissues, suggesting its potential involvement in malignant transformation or tumorigenesis. Speci cally, S100A16 overexpression has been observed in bladder, lung, thyroid, pancreatic, glioma, and ovarian tumors [12,20]. Functionally, S100A16 is involved in various aspects of tumorigenesis, including cell proliferation, differentiation, migration, invasion, and epithelial-mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S100A16, a calcium-binding protein, is widely expressed in tumor tissues, suggesting its potential involvement in malignant transformation or tumorigenesis. Speci cally, S100A16 overexpression has been observed in bladder, lung, thyroid, pancreatic, glioma, and ovarian tumors [12,20]. Functionally, S100A16 is involved in various aspects of tumorigenesis, including cell proliferation, differentiation, migration, invasion, and epithelial-mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, previous studies assessed the potential prognostic signi cance of S100A16 in various cancer types [12]. Interestingly, S100A16 has been proposed as a potentially useful prognostic marker for evaluating the effectiveness of adjuvant chemotherapy based on platinum in patients who underwent surgical resection of lung cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…These genes serve an important biological role in the occurrence and development of tumors. Among these genes, S100A16 is highly conserved in mammals ( 32 ), and its high expression is linked with tumor cell growth and EMT ( 33 ). S100A16 is a prognostic marker for various tumors, including LUAD and colorectal cancer ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses based on BC cell lines have shown that Snail, the EMT-related transcription factor, regulates S100A16 [25]. The knockdown of S100A16 was shown to reduce the expression of N-cadherin, vimentin, and slug and increase the expression of E-cadherin in BC cells [10,26]. S100A16 may directly or indirectly act to EMT associated marker and induce EMT.…”
Section: Discussionmentioning
confidence: 99%